Functional analysis of the Escherichia coli mrdA gene in melittin resistance - Zhao, Chong-Yi; Li, Xiao; Zhao, Ting; Liu, Ying; Xia, Xue-Shan; Wu, Xiao-Mei (Frontiers in Microbiology, 2025)
ObjectiveThe aim of this study is to examine the functional role and resistance mechanisms of the Escherichia coli (E. coli) peptidoglycan transpeptidase gene, mrdA, in resistance to melittin.MethodsThe resistance of E. coli strains with either knockout or overexpression of the mrdA gene to melittin was initially assessed. The differences in melittin absorption between these two strains were evaluated following depletion and heterologous expression of the mrdA gene. Subsequently, peptidoglycan was extracted from the strains to determine its capacity to adsorb melittin. Finally, the morphological changes in different strains induced by melittin exposure were examined under scanning electron microscopy. These analyses served to validate the role of peptidoglycan transpeptidase mrdA in melittin resistance and to hypothesize its potential resistance mechanism.ResultsThe results clearly indicated a direct correlation between the degree of peptidoglycan cross-linking in E. coli and its enhanced resistance to melittin. Specifically, we found that increased cross-linking of peptidoglycan led to a thickening of the bacterial cell wall and a reduction in pore size. These structural changes potentially decrease the damage to the cell wall caused by melittin, as the thicker cell wall and smaller pores reduce the ability of melittin to penetrate and access the interior of bacterial cells. This mechanism effectively limits the contact between melittin and bacterial components, minimizing its destructive effects, and thereby conferring resistance to melittin in the bacteria.ConclusionThis study is the first to elucidate the role of peptidoglycan in the cell wall of E. coli in the context of antimicrobial peptide resistance. Novel ideas have been proposed for the development of antibacterial drugs targeting the peptidoglycan of Gram-negative bacteria.